Establishing a comprehensive panel of patient-derived xenograft models for high-grade endometrial carcinoma: molecular subtypes, genetic alterations, and therapeutic target profiling - Sho Sato; Shigehiro Yagishita; Hiroshi Yoshida; Daisuke Shintani; Aiko Ogasawara; Tadaaki Nishikawa; Masanori Yasuda; Keiji Furuuchi; Toshimitsu Uenaka; Akinobu Hamada; Kosei Hasegawa (Neoplasia: An International Journal for Oncology Research)
Background: High-grade endometrial cancer (EC) has a poor prognosis, but molecular classification-based treatments present new therapeutic opportunities. Antibody-drug conjugates (ADC) emerge as promising tools, yet a deeper understanding of antigen dynamics, optimal therapeutic sequencing, and resistance mechanisms is essential. This study investigates the utility of patient-derived xenograft (PDX) models for EC as preclinical platforms, evaluating molecular subtypes and the ADC targets expression of patient and PDX tumors. Methods: We developed a comprehensive panel of molecularly characterized PDX models from patients with EC representing various histological types. Molecular subtypes and gene alterations were analyzed using sequencing and immunohistochemistry. ADC targets, including human epidermal growth factor receptor 2, trophoblast cell-surface antigen 2, B7-H4, folate receptor alpha, and cadherin-6, were profiled. Results: Thirty-one EC-PDX models were successfully established, maintaining histological fidelity and 93.1 % molecular subtype consistency with the patient tumors. Notably, 80.6 % of the PDX models exhibited high expression (2+/3+) of at least one ADC target, and 54.8 % displayed high expression of multiple targets. Remarkably, 9.7 % showed high expression of all targets, with gene mutations also characterized. Meanwhile, patient tumors, 78.8 % showed high expression (2+/3+) of at least one ADC target, and 63.6 % showed high expression of multiple targets. Conclusion: The molecularly classified EC-PDX panel, enriched with detailed antigen profiles and genetic data, provides a robust platform for investigating novel ADC therapies and precision treatment strategies for high-grade EC.